Participation of women in technology innovation projects in Croatia - Lažnjak, Jasminka; Šporer, Željka; Švarc, Jadranka (2008)
The paper presents a social profile of women and possible gender differences among Croatian researchers who participated in Croatian program of technology innovation development (HITRA). The article presents some preliminary data from the project “ Social Evaluation of Croatian Innovation System in the Function of Knowledge Society” financed by Ministry of science, education and sport. The aim of this still ongoing project is to explore how social and cultural environment factors influence and shape innovation process by exploring the performance of certain innovation policy instruments in Croatia. Part of the project was a survey on different aspects of the technology innovation program for participants in the program HITRA. The questionnaire was targeted at scientists from various scientific disciplines who have participated in the “ Croatian innovation and technological development Program” and the following aspects were questioned: individual characteristics, scientific and social profiles, characteristics and typology of the projects in the domain of public-private partnership, typology of social networks, attitudes towards the exiting innovation policy measures in Croatia (expectations, disappointments, obstacles, success and criteria of success) The paper will explore possible gender differences in social and research profile of women scientists who successfully applied and finished technological projects, i.e. women who wanted to develop innovative products and solutions and commercialize their knowledge. The main focus will be on issues such as: Do women innovators follow the same pattern known in many previous researches on gender differences in research productivity and position of women in social organization of academia? Is the same “ glass ceiling” present here? From which disciplines are they coming? What is their level of success in technology projects compare to men? These dimensions will be correlated with different types of values like egalitarianism, traditionalism, statism, openness and international integration, and market orientation. The paper will try to explore the role of women in the process of building knowledge based society, the position of women scientists in a specific but more and more significant type of research productivity, in capitalization of knowledge and use of knowledge in generating innovations.
Projekt MZOS
Projekt MZOS
ENG